Adults with Learning Disabilities - Sami El Ahmadie (Adult Education Research Conference, 2022)
In this literature review, I seek to shed light on the struggles faced by adults with learning disabilities in two particular areas: Employment and Stigma.
Keywords: Learning Disabilit; Employment; Stigma; Adults